Scaling Up Renewable Geothermal Energy in Indonesia - World Bank (Washington, DC, 2014)
Pertamina Geothermal Energy (PGE) is leading Indonesia s effort to scale-up geothermal, attempting a globally unprecedented expansion of over 1,000 MW of capacity. The World Bank is helping kick-start PGE s investment program through the development of the Ulubelu (Units 3 and 4) and Lahendong (Tompaso) (Units 5 and 6) geothermal fields. Loans totaling US$ 300 million are being extended from the World Bank s facility for lending to middle-income countries through International Bank for Reconstruction and Development (IBRD) loans and from the global Clean Technology Fund (CTF) established to promote climate-friendly investments. To justify public support and evaluate the viability of this green finance investment, an integrated approach to decision making was utilized based on the combined assessments of financial-economic-stakeholder-risk impacts.